Positive Criminology and Positive Psychology. (February 2023) - Olson, Jeremy
Welcome to our Special Issue on Positive Criminology and Positive Psychology. It is our hope that this issue will help generate critical reflection about American criminal justice policy and the possibility of moving the system towards a happier and more prosocial perspective. To begin, this editorial introduction briefly frames positive criminology and positive psychology for the readers, and then reviews the content of the special issue.